METODE PERANCANGAN 3E (ECO-EFE-EFI) PADA PROYEK AKHIR MAHASISWA: SUATU PENDEKATAN SISTEMATIS - Bayu Rahmat Setiadi (Universitas Sarjanawiyata Tamansiswa, 2015)
The design method was found a lot at the time the student will face a final project. Methods of existing designs such as: the method developed Holtzapple; Pahl & Beitz; Nigel Cross; Ibrahim Zeid; Dieter & Schmidt; and many more are choices that are often used in developing the students' final projects. The inconsistency of students in each passing step by step in the design step provides a product which is manifested not in accordance with the preliminary design of the designer and the needs of the market. Therefore, the design method that has a value of 3 E (Economies, Effective, and Efficience) through 7 (seven), namely: (1) analyze the needs of the market; (2) develop structuring issues; (3) gathering information; (4) identify the needs of the designer; (5) develop design concepts; (6) realize the design; and (7) compose the image detail to be done in a systemic, sequence, and structured.